The Behavior Analysis For Washing Hands With Soap And Indiscrimniate Defecation Against Diarrhea In Soe City Sub District Area South Central Timor - Sammytampani, Ofrin; Indasah; As'ad Efendy, Mohamad (Journal of Global Research in Public Health, 2019)
Diarrhea can spread through unhygienic behavior, such as preparing food with unwashed hands after bowel movements or allowing a child to play in areas where there is contaminated feces. The purpose this study has purpose to know the behavior analysis for washing hands properly and indiscriminate defecation against diarrhea in Soe City Sub District Area South Central Timor. The design of this study was observational with cross sectional approach. The population studied by all people with diarrhea in Soe Sub-District of South Central Timor was 135 people, with cluster random sampling technique obtained 101 respondents. Independent variables were washing hand properly and indiscriminate defecation behavior with dependent variable diarrhea incidence. Data were collected using questionnaires. Data analysis by Ordinal Regression test at α = 0,05. The result shows that most of respondent have washing hands properly in enough category, amount 73 respondent (72,3%), most of respondent have indiscriminate defecation in no indiscriminate category, amount 68 respondent (67,3%) and most respondents had diarrhea incidence in the light category, amount 92 respondents (91,1%). The analysis results using ordinal regression test obtained p-value (0.001) < α (0.05) so H0 rejected and H1 accepted which means there is influence of washing hands properly and indiscriminate defecation against diarrhea in Soe City Sub District Area South Central Timor. Hand washing is the ultimate action and the only way to prevent the onset of the disease. Diarrheal disease was associated with water conditions, but accurately it should be considered also the handling of human feces such as feces and urine, because the germs that cause diarrhea come from these impurities.